Evaluation of the Diagnostic Potential of Liver Aminotransferases and Alkaline Phosphatase in Patients with Cardiovascular Diseases - Yadav, N. K.; Pokharel, D. R.; Kathayat, G.; Sigdel, M.; Hussain, I. (Kathmandu University Medical Journal, 2022)
Background Cardiovascular diseases (CVDs) are the major cause of morbidity and mortality, particularly in developing countries. Early diagnosis with the best diagnostic marker is highly desired for the prevention and timely treatment of CVDs. However, there is still a dearth of an ideal marker for the detection of CVDs. Objective To explore the diagnostic potential of liver aminotransferases (AST and ALT), and alkaline phosphatase for the diagnosis of CVDs without liver involvement. Method This was a cross-sectional study conducted among 200 adult patients with CVDs, who visited the cardiology and emergency units of Manipal Teaching Hospital, Pokhara, Nepal. The study was conducted from January 2018 to December 2020. The baseline data on family history, anthropometry, baseline biochemical parameters, liver enzymes, and cardiac biomarkers were collected using standard and validated methods. The data were analyzed using SPSS version 21 and MedCalc software 2021. Result The diagnostic sensitivity of aspartate aminotransferase, alanine aminotransferase and alkaline phosphatase were 53.7%, 52.6%, and 33.7% and specificity were 99%, 90%, and 90% respectively. The area under the curve (AUC) of AST, ALT, and ALP were 0.78, 0.73, and 0.52 respectively. ROC curve indicated that serum AST and ALT activity was a better reliable marker than the serum ALP activities. Conclusion Our study suggests that serum aspartate aminotransferase and alanine aminotransferase but not alkaline phosphatase could have some diagnostic potential to diagnose the risk of CVDs. However, they could not replace the currently adopted cardiac biomarkers such as cTnI and CK-MB.